The 1927-1938 Italian archaeological expedition to Transjordan in Renato Bartoccini's archives - Anastasio, Stefano (Archaeopress archaeology., 2015)
This volume presents the results of the Italian excavations and surveys carried out in Transjordan between 1927 and 1938.